Marketing Strategy for Higher Education Institution Based On Marketing Stimuli (Case Study at Politeknik Pos Indonesia) - Senny Handayani Suarsa; Muhammad Meki Munawar (Universitas Kristen Satya Wacana, 2020)
The purpose of this study is to examine whether marketing strategies based on the marketing stimuli of higher education services influence the selection of the Politeknik Pos Indonesia as higher education institution to continue their studies, as well as which of these marketing mix factors is most influential. The data collection was carried out by an independent survey involving 356 Politeknik Pos Indonesia students. The results showed that all variables had a significant influence on the decision making of the Politeknik Pos Indonesia by prospective students. Hence, the first and second hypotheses are proven by the most influential factor is the product.